Using Lotteries to Incentivize Safer Sexual Behavior : Evidence from a Randomized Controlled Trial on HIV Prevention - Björkman Nyqvist, Martina; Corno, Lucia; de Walque, Damien; Svensson, Jakob (World Bank Group, Washington, DC, 2015)
Financial incentives are a promising HIV prevention strategy. This paper assesses the effect on HIV incidence of a lottery program in Lesotho with low expected payments but a chance to win a high prize conditional on negative test results for sexually transmitted infections. The intervention resulted in a 21.4 percent reduction in HIV incidence over two years. Lottery incentives appear to be particularly effective for individuals willing to take risks. This paper estimates a model linking sexual behavior to HIV incidence and finds that risk-loving individuals reduce the number of unprotected sexual acts by 0.3/month for every $1 increase in the expected prize.